Minutes of the Meeting of the Executive Committee Chicago, IL April 27, 2012 - Siegfried, John J. (American Economic Review, 2013)
The first meeting of the 2012 Executive Committee was called to order at 10:01 a.m. on April 27, 2012 in the Writer Room of the Renaissance O’Hare Hotel, Chicago, IL. Members present were: Orley Ashenfelter, Alan Auerbach, Janet Currie, Pinelopi Goldberg, Claudia Goldin, Jonathan Gruber, Robert Hall, Anil Kashyap, Rosa Matzkin, Christina Paxson, Monika Piazzesi, Andrew Postlewaite, Valerie Ramey, Nancy Rose, John Siegfried, Christopher Sims, and Michael Woodford. Executive Committee members David Autor and Esther Duflo participated in parts of the meeting by phone. Caroline Hoxby participated in part of the meeting and Abhijit Banerjee and Vincent Crawford participated by phone as members of the Honors and Awards Committee. Angus Deaton participated in part of the meeting as chair of the Nominating Committee. Associate Secretary-Treasurer Peter Rousseau also attended. Sims welcomed the newly elected members of the 2012 Executive Committee: Claudia Goldin, President-elect; Christina Paxson and Nancy Rose, Vice-presidents; and Anil Kashyap and Rosa Matzkin, and recognized the Secretary at the last meeting of his 16-year tenure. The Minutes of the January 5, 2012 meeting of the Executive Committee were approved as written. Report of the Secretary (Siegfried). Siegfried reviewed the schedule for sites and dates of future meetings: San Diego, January 4–6, 2013 (Friday, Saturday, and Sunday); Philadelphia, January 3–5, 2014 (Friday, Saturday, and Sunday); Boston, January 3–5, 2015 (Saturday, Sunday, and Monday); San Francisco, January 3–5, 2016 (Sunday, Monday, and Tuesday); Chicago, January 6–8, 2017 (Friday, Saturday, and Sunday); Atlanta, January 5–7, 2018 (Friday, Saturday, and Sunday); Philadelphia, January 4–6, 2019 (Friday, Saturday, and Sunday); and San Diego, January 3–5, 2020 (Friday, Saturday, and Sunday). The Executive Committee meets the day prior to the Annual Meeting each year. Minutes of the Meeting of the Executive Committee Chicago, IL April 27, 2012